The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/10408398.2017.1400517
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, human health and winemaking perspectives

Abstract: Resveratrol, (3, 5, 4'-trihydroxystilbene) is a non-flavonoid polyphenol stilbene synthesized by plants when damaged by infectious diseases or ionizing radiation. Although present in more than seventy plant species, grapes and wine are the major dietary contributors of resveratrol, responsible for 98% of the daily intake. In 1992, Renaud and De Lorgeril first linked wine polyphenols, including resveratrol, to the potential health benefits ascribed to regular and moderate wine consumption (the so called "French… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 116 publications
0
41
0
1
Order By: Relevance
“…Polyphenols are the most important wine antioxidants; their natural content varies significantly and depends on the region, grape variety or varietal, soil, climate, irrigation, harvest, performance, winemaking, ripening and storage. Frankel and co-workers [21][22][23] showed that the TAP of wine could be correlated to the inhibition of LDL cholesterol oxidation. The postprandial period is the phase where reactive oxygen species increase mostly, due to the digestion and metabolism of food [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenols are the most important wine antioxidants; their natural content varies significantly and depends on the region, grape variety or varietal, soil, climate, irrigation, harvest, performance, winemaking, ripening and storage. Frankel and co-workers [21][22][23] showed that the TAP of wine could be correlated to the inhibition of LDL cholesterol oxidation. The postprandial period is the phase where reactive oxygen species increase mostly, due to the digestion and metabolism of food [23].…”
Section: Resultsmentioning
confidence: 99%
“…Frankel and co-workers [21][22][23] showed that the TAP of wine could be correlated to the inhibition of LDL cholesterol oxidation. The postprandial period is the phase where reactive oxygen species increase mostly, due to the digestion and metabolism of food [23]. There are data showing that moderate wine consumption with meals could decrease the metabolic risk associated with the absorption of free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, grapes are a good source of polyphenols: the peel and pulp of grapes contain mainly anthocyanins (red varieties) and flavonols, while seeds are rich in procyanidins. Although the health-promoting effects of these compounds have been widely investigated, especially in cardiovascular area, diabetes and neurodegenerative disorders [4,5], few studies have been performed about their effect on gastric inflammation. One of the main causes of gastritis is the Helicobacter pylori (H. pylori) infection; this gram-negative bacterium colonizes at least 50% of the world human population [6].…”
Section: Introductionmentioning
confidence: 99%
“…Certain bioactive molecules present in grapes and wines are particularly relevant to human health because of their antioxidant potential. It is reported that polyphenols (like resveratrol, quercetin, and quercitrin) show high antioxidant [10][11][12][13], anticancer [14][15][16][17], and cardiovascular system protective activities [18][19][20][21] and play important roles in human oral microbiota preservation [22]. Due to its anthocyanins and polyphenols components, wine is comparable, in terms of antioxidant properties to natural and enriched formulations [18,19,23].…”
Section: Introductionmentioning
confidence: 99%